Discursive construction of public assembly in the pre-election discourse of Malaysian mainstream print newspaper - Parveen Kaur Gill (2014)
The Malaysian mainstream print newspapers (henceforth MMPN) are owned by conglomerates closely affiliated to the ruling coalition parties and the state. Thus, the MMPN is a powerful instrument which the newspaper owners can use to (re)construct reality for the masses by advancing the views and ideologies of the political parties to which they are affiliated and help the state to secure hegemony and the consent of the masses. Recognising this important role of the MMPN, this study investigated critically the language used in the pre-election discourse of two pro-establishment dailies to address the issues of public assembly during a one-year period beginning June 1, 2011, prior to the 13th General Election. By means of qualitative content analysis, this study explored the prevalent themes and topics in the heading, sub-heading and lead (news abstract) of the front page and page lead news articles of the New Straits Times (NST) and The Star and how various discursive strategies, and as well as their related linguistic means were employed with a view to unveil the ideologies that appeared to underpin the pre-election discourse practices of the newspapers. The discourse analysis framework adopted for this study was based on the Critical Discourse Analysis approaches espoused by Fairclough, Van Dijk, and Wodak in tandem with theories and ideas from mass media studies, particularly the agenda-setting theory. A total of 352 news texts containing words such as “gathering”, “assembly”, “rally”, “demonstration”, “protest”, “strike” and related epithets were identified of which two major issues were discerned–the legitimacy of demonstrations or gatherings, as well as the tabling and passing of the Peaceful Assembly Bill 2011. The thematic analysis of the news texts revealed six prevalent themes in the discursive construction of public assembly: 1) the constructions of menace and public nuisance; 2) legitimate versus illegitimate motivation; 3) unsuitable venues; 4) disruption of legitimate order; 5) police violence as untrue or provoked; and 6) the state in support of freedom of assembly. Furthermore, discursive strategies such as referential strategies, predication strategies and argumentation strategies were employed to justify, legitimise and naturalise the social exclusion of the Other and to have action taken against “Them”. The ideological representation of the Other was linguistically realised through lexicalization and the overall consequence of the discourse themes, strategies and their related linguistic means was negative representation of “Them” while “We” were portrayed positively. It was concluded that in the run-up to the 13th GE, the MMPN discursively constructed the issues of public assembly in favour of Barisan Nasional or National Front and against either those who appeared to threaten the status quo of the state or those who were directly or indirectly affiliated to Pakatan Rakyat (People’s Alliance) or Opposition Front.